Nanostructured grating patterns over a large area fabricated by optically directed assembly. Issue 27 (24th June 2016) - Huang, Xiaoping; Chen, Kai; Qi, Mingxi; Li, Yu; Hou, Yumeng; Wang, Ying; Zhao, Qing; Luo, Xiangang; Xu, Qingyu
Abstract : An optically directed assembly route is proposed for bottom-up fabrication of stable nanostructured grating patterns in solution using laser standing evanescent wave fields. Abstract : Optical trapping and manipulation of nanoparticles (NPs) have been widely used in nanotechnology and biology. Here, we demonstrate an optically directed assembly (ODA) route for bottom-up fabrication of stable nanostructured grating patterns in solution using laser standing evanescent wave (LSEW) fields. The control mechanism is the intriguing cooperative action of the periodically line-centered attractive optical gradient force and the near field dipolar coupling force induced by LSEW, which leads to assembly of the colloidal silver NPs into robust grating patterns within minutes. The anisotropic polarization nature of the grating patterns was studied further by examining the morphology correlation of the surface-enhanced Raman scattering (SERS)-based signal amplification. We show the LSEW ODA method can optimize and stabilize the strongest dipolar coupling style among the NPs during pattern assembly. These results advance the further understanding of ODA of colloid NPs and might have many potential applications in SERS, catalysis, nanophotonics and nano-fabrication.